Pengaruh Penggunaan Model Pembelajaran Berbasis Proyek “Project Based Learning” Terhadap Hasil Belajar Fisika Peserta Didik Kelas X IPA SMA Negeri 35 Halmahera Selatan Pada Konsep Gerak Lurus” - Susi Ismail (Peneliti.net, 2022)
This research is an experimental study that aims to determine whether or not the use of a project based learning model has an effect on the physics learning outcomes of class X students at SMA Negeri 35 Halmahera Selatan on the concept of straight motion and to find out how much increase in physics learning outcomes the participants have. students of class X science at SMA Negeri 35 Halmahera Selatan using a project-based learning model on the concept of straight motion in the 2019-2020 school year which consists of one study room/classroom totaling 26 students so that they are divided into two groups for classes. experimental and control classes. This type of research is a quasi-experimental research using a nonequivalent control group design and the sampling technique used is a purposive sample. The sample used was 13 students in the experimental class and 13 students in the control class. The instrument used is a test instrument in the form of a multiple choice objective test with 20 questions with a score of 0-1. The results of this study were tested with statistics through the IBM SPSS version 26 application program